Force Constants of Cu Crystals from Diffuse Neutron Scattering Measurement - T. Sakuma; S.R. Mohapatra; H. Uehara; R. Sakai; Xianglian Xianglian; H. Takahashi; N. Igawa; K. Basar (Atom Indonesia, 2010)
Diffuse neutron scattering measurement on Cu crystals was performed at 10 K and 300 K. Oscillatory forms were observed in the diffuse scattering intensities. The observed diffuse scattering intensities are analyzed by including the correlation effects among thermal displacements of atoms in the theory. Using the values of correlation effects among neighboring atoms and the values of Debye-Waller temperature parameter, force constants among first, second and third nearest neighboring atoms have been evaluated. The result of correlation effects in Cu crystals are compared to that of ionic crystal and semiconductor. The relation between correlation effects and the inter-atomic distance is not depending much on the crystal binding types. Received: 12 October 2010; Revised: 22 October 2010; Accepted: 16 December 2010